2021
DOI: 10.1016/s2213-2600(21)00263-0
|View full text |Cite|
|
Sign up to set email alerts
|

Azithromycin versus standard care in patients with mild-to-moderate COVID-19 (ATOMIC2): an open-label, randomised trial

Abstract: Background The antibacterial, anti-inflammatory, and antiviral properties of azithromycin suggest therapeutic potential against COVID-19. Randomised data in mild-to-moderate disease are not available. We assessed whether azithromycin is effective in reducing hospital admission in patients with mild-to-moderate COVID-19. MethodsThis prospective, open-label, randomised superiority trial was done at 19 hospitals in the UK. We enrolled adults aged at least 18 years presenting to hospitals with clinically diagnosed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 32 publications
0
48
1
3
Order By: Relevance
“… 23–25 In two studies, patients were treated with 500 mg/day for 10 days. 18 , 26 In one study, patients received 500 mg/day for 14 days 27 and in another one 500 mg/day for 3 days. 28 All studies compared the outcomes of patients treated with azithromycin against those for the ones that had only received standard care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 23–25 In two studies, patients were treated with 500 mg/day for 10 days. 18 , 26 In one study, patients received 500 mg/day for 14 days 27 and in another one 500 mg/day for 3 days. 28 All studies compared the outcomes of patients treated with azithromycin against those for the ones that had only received standard care.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis showed no difference in death for those treated with or without azithromycin, in observational studies [OR: 0.90 (0.66–1.24)], RCTs [OR: 0.97 (0.87–1.08)] and when studies with both designs were pooled together [OR: 0.95 (0.79–1.13)] ( Figure 2 ). In the study by Hinks and colleagues, 27 the outcome was death or need for admission, and this was used as a proxy for death in the meta-analysis. Excluding this study had minimal effect on the magnitude and the significance of the results, with an overall OR 0.95 (0.79–1.14).…”
Section: Resultsmentioning
confidence: 99%
“…A massive use of azithromycin was observed even in asymptomatic patients during the study period, although a large body of evidence documented that this drug is not effective in reducing the risk of COVID-19-related outcomes [ 17 ] or the time to recovery, when compared to the standard care alone [ 18 ]. It was also demonstrated that, when compared to placebo, the treatment with a single dose of azithromycin was not associated with a greater likelihood of being symptom-free within two weeks among outpatients with SARS-CoV-2 infection [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO Solidarity Trial interim results showed that hydroxychloroquine, lopinavir, remdesivir and interferon beta‐1a had no impact on mortality, hospitalisation duration or initiation of ventilation support in COVID‐19 patients. 7 Among other drugs considered for repurposing, neither azithromycin, 8 metformin 9 nor favipiravir 10 demonstrated significant benefit in the treatment of COVID‐19 patients. Large controversies currently exist around the use of ivermectin in COVID‐19, 11 but both the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) advise against its use for the prevention or treatment of COVID‐19 outside of randomised clinical trials.…”
Section: Introductionmentioning
confidence: 99%